Strength performance of cement/slag-based stabilized soft clays. (30th June 2019) - Liu, Li; Zhou, Annan; Deng, Yongfeng; Cui, Yujun; Yu, Zhao; Yu, Chuang
Highlights: The binder with steel slag, cement, and metakaolin is efficiently used to stabilize soft clay. The existed clay mineral in soils absorbs the water and changes the water formation in the binder-soil mixture. The binder-free water ratio is proposed to explicit the strength performance of the stabilized soils. A unified analysis frame was attempted to unify the strength performance of concrete, mortar and stabilized soil. Abstract: This paper presents an experimental study on the strength behaviour of the soils stabilized by the composite of steel slag, cement and metakaolin (SCM composite), at different clay fractions, water contents and curing periods. The SCM composite can effectively improve the soil strength and the SCM stabilized soil shows the similar property to cemented soils. The microstructures of SCM stabilized soils with different curing periods and water contents are also presented via scanning electron microscope tests. Comparing the microstructure and fissure between stabilized soils, mortar and concrete, it is clear that the non-free water absorbed at the surface of clay minerals does not involve the hydration/pozzolanic process. Moreover a new variable, the free water content, is proposed, which equates to total water content subtracts n times of plastic limits of the original soils. The free water content is effectively employed to characterize the unconfined compression strength of stabilized soils observed in this research and also in literatures. With this proposed concept, the binder stabilized soils can be accommodated by the framework for traditional cementitious material (concrete and mortar).